Design And Construction Of Automatic Transfer Switch (ATS) System With Backup Control System In Hybrid Power Plant (PLN - PLTS - GENSET) - Gavrila Mailuhu, Jevon; A.F. Haurissa, Marceau; Jamlaay, Marselin (Publisher Cv. Inara, 2025)
PLN's electricity supply is not always continuous in the process of distributing power, because under certain conditions there will be blackouts caused by interruptions or maintenance in the distribution system. An alternative to overcome PLN disturbances is to use renewable sources such as solar power plants and generators with an ATS automatic control system controlled using PLC. This study conducted a literature study to collect relevant theories and references about this research. PLC diagram leaders are designed for the process of transferring PLN, PLTS and Generator to load electrical power. Solar power plants operate during disruptions to PLN resources during operational hours (10 a.m. – 3 p.m.) and generators operate when solar power resources cannot supply to the load and at night outside solar power plant operating hours. The ATS system is able to switch the process of switching PLN and PLTS power sources very quickly without any time lag so that the load is directly supplied by PLN and PLTS power sources. The process of switching the generator source takes approximately 2 seconds for the starting process. The process of transferring battery power resources to critical loads without any time lag during the generator starting process and when generator starting failure occurs.